Comparison of metabolic responses to the mixed meal tolerance test vs the oral glucose tolerance test after successful clinical islet transplantation. Issue 8 (22nd June 2018) - Forbes, Shareen; Lam, Anna; Koh, Angela; Imes, Sharleen; Dinyari, Parastoo; Malcolm, Andrew J.; Shapiro, A. M. James; Senior, Peter A.
Abstract: Following islet transplantation, mixed meal tolerance tests (MMTs) are routinely utilized to assess graft function, but how the 90‐minute MMTT glucose value relates to a 120‐minute glucose concentration of ≥11.1 mmol/L used to diagnose diabetes following a standardized 75 g‐OGTT, is not known. We examined this relationship further. Thirteen subjects with Type 1 diabetes and stable transplant grafts, not on exogenous insulin with HbA1c < 7% (53 mmol/mol), were studied on 17 occasions with paired OGTTs and MMTTs. Receiver operating characteristic (ROC) curves were constructed to derive the 90‐minute MMTT glucose threshold associated with a 120‐minute glucose concentration following a 75 g‐OGTT (OGTT120 ) ≥11.1 mmol/L and their diagnostic accuracy. Studies with OGTT120 ≥11.1 mmol/L (n = 5) had diminished C‐peptide: glucose, greater integrated glucose and diminished insulin: glucose area under the curve (AUC) ratios (0‐120 minutes) and disposition indices; all P  < .05, contrasting with MMTTs where no difference in the 90‐minute glucose concentrations, C‐peptide:glucose, integrated glucose, C‐peptide and C‐peptide: glucose AUCs (0‐90 minutes) was seen; all P  > .05. A 90‐minute MMTT glucose concentration ≥8.0 mmol/L demonstrated a sensitivity and specificity of ≥80% for the diagnosis of OGTT120 ≥11.1 mmol/L; area under ROC curve (mean ± SEM) 73 ± 13%. A 90‐minute MMTT glucose ≥8.0 mmol/L, identifies islet transplant recipients who may require closer monitoring for graft dysfunction.